Johnson graphs are Hamilton-connected - Alspach, Brian (Ars mathematica contemporanea, 2013)
We prove that the Johnson graphs are Hamilton-connected and apply this to obtain that another family of graphs is Hamilton-connected.
Keywords: Hamilton path; Hamilton-connected; Johnson graph